Modulation of a rapid neurotransmitter receptor-ion channel by membrane lipids - Barrantes, Francisco J. (Frontiers in Cell and Developmental Biology, 2024)
Membrane lipids modulate the proteins embedded in the bilayer matrix by two non-exclusive mechanisms: direct or indirect. The latter comprise those effects mediated by the physicochemical state of the membrane bilayer, whereas direct modulation entails the more specific regulatory effects transduced via recognition sites on the target membrane protein proper. The nicotinic acetylcholine receptor (nAChR), the paradigm member of the pentameric ligand-gated ion channel (pLGIC) superfamily of rapid neurotransmitter receptors, is modulated by both mechanisms. Reciprocally, the nAChR protein exerts influence on its surrounding interstitial lipids. Folding, conformational equilibria, ligand binding, ion permeation, topography, and diffusion of the nAChR are modulated by membrane lipids. The knowledge gained from biophysical studies of this prototypic membrane protein can be applied to other neurotransmitter receptors and most other integral membrane proteins. neurotransmitter receptor families: the nicotinic acetylcholine receptors (nAChRs), the γaminobutyric acid(type A and C) receptors, the glycine receptors, subtype 3 of the serotonin receptor family, and the glutamate-gated chloride channel (Zoli et al., 2018). pLGICs are built following a common architecture: five subunits in a pseudo-symmetric layout surrounding an ionpermeation pathway, the ionic pore. The structural similitude is related to the evolutionarily history and conservation of these membrane-bound proteins (